ANALYSIS OF THE REAL SECTOR OF THE ECONOMY OF THE REPUBLIC OF KAZAKHSTAN AND ITS DEVELOPMENT PROSPECTS - R.S. Bespayeva,; B.Beisengaliyev,; A.N.Turekulova,; Z.E. Nurgaliyeva,; G.B.Bermukhamedova,; D.M.Turekulova, (Academic Journal of Physical and Chemical Sciences, 2019)
The real sector of the economy is the industrial production sector of the Republic, which includes a large number of enterprises of various sectors of economic development of the Republic of Kazakhstan. Analyze the real sector of the economy of the Republic of Kazakhstan and consider the prospects for its development. The article presents an attempt to describe and classify these enterprises, to determine their role in the development of the economy. In this article the authors analyzes the features of the development of the real sector of the economy of the Republic of Kazakhstan in the long term-from 1996 to 2017. Тhe article also provides an analysis of the perspective directions of development of the real sector of the economy, as well as the main content and limitations of each of them. When conducting foresight studies, a combination of 10–15 forecasting methods is used. For visual systematization of Foresight methods by a specialist of the University of Manchester R. Popper, a scheme was developed, called the "Foresight-rhombus".